SIFAT FISIS DAN STABILISASI DIMENSI BEBERAPA JENIS BAMBU KOMERSIAL - Barly; Agus Ismanto; Dominicus Martono; Abdurachman; Andianto (BRIN Publishing, 2012)
This experiment aims to look into appropriate formulate which may improve physical properties and dimentional stability of bamboos to optimize their uses as construction materials. Results revealed that length of culm (stem), number of internodes, and internode length varied in accord with different bamboo species. Moisture content of bamboo varied depending on species, ie.bijan or ater (236.15%), mayan (181.52%), tali (117.32%), and hitam (111.83%). Likewise, bamboo density also varied, ie, tali (0.93), andong (0.88), mayan (0.83), bijan or ater (0,79), hitam (0.78), and betung (0.78). The density of bamboo decreases in cross-section moving, from the periphery, middle to inner part. Volumetric shrinkage varieds according to bamboo species, i.e. mayan (9.04%), betung (15.75%), andong (16.32%), and ater (38,45%). The bigbest ASE percentage (95.57%) occured at ater (LO), while the lowest (-144,92%) was of mayan (SCa). Bamboo that afford responses to ASE percentage value was arranged from the bighest, i.e. LO, PEG, SPA, B, A, C. The LO agent was absorbed the least by all bamboo species, followed in increasing order by PEG with the expection of hitam hamboo, Bamboo that absorbed the swell-resisting order by PEG with the least was the andong (14.22%) with LO, and the greatest inflicted by bitam (137,54%) with PEG, Almost all bamban species were able to absorb the entire swell-resisting agents in large amount. The retention of agents in dry bamboo was arranged in order from the bigbest to the Inwest, ie. PEG, LO, SCa, and SPo The highest to the lowest retentions were of consecutively hitam, ater, tutul, andang, mayan, and betung.